Analisis Penerapan PSAK 109 Pada Pelaporan Keuangan Zakat di Lembaga Amil Zakat - Rezki Romadhan; Yulia Auci Anugrah; Kiki Agusteri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the extent to which Statement of Financial Accounting Standards (PSAK) 109 on Zakat Accounting has been implemented in the financial reporting of Amil Zakat Institutions. PSAK 109 is designed as a guideline to ensure that the management of zakat, infaq, and alms funds is carried out in an accountable, transparent, and Sharia-compliant manner. The research employs a qualitative descriptive approach, using in-depth interviews, observation, and documentation as data collection techniques, allowing for a comprehensive exploration of zakat accounting practices applied by the institution. The findings indicate that the Amil Zakat Institution has implemented most aspects of PSAK 109, particularly in the recognition, measurement, and presentation of zakat funds, which are clearly separated from non-zakat funds. This practice demonstrates a positive effort by the institution to maintain accountability and transparency in managing public funds. However, the study also reveals weaknesses in the disclosure aspect, especially in the Notes to Financial Statements (CALK), where the information provided remains limited and has not fully met the requirements of PSAK 109. Such limitations reduce the overall quality and transparency of financial reporting. The main challenges in implementing PSAK 109 include the limited number of human resources with sufficient technical knowledge of zakat accounting, the inadequacy of the existing accounting information system, and the lack of intensive technical training. These issues hinder the optimal application of PSAK 109 and may lead to inconsistent interpretations in practice. Therefore, strategic improvements are required through internal capacity building, the development of integrated accounting information systems, and continuous assistance from relevant authorities. These efforts are expected to enhance the quality of zakat financial reporting, making it more transparent, accountable, and Sharia-compliant, while also strengthening public trust in Amil Zakat Institutions as trustworthy managers of public funds.